2012
DOI: 10.12659/msm.883204
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heat treatment on H2O2/HCl etched pure titanium dental implant: An in vitro study

Abstract: SummaryBackgroundSurface chemistry of dental implant plays an important role in osseointegration. Heat treatment might alter surface chemistry and result in different biological response. The aim of this study was to investigate the roles of heat treatment of H2O2/HCl-treated Ti implants in cell attachment, proliferation and osteoblastic differentiation.Material/MethodsSandblasted, dual acid-etched and H2O2/HCl heat-treated discs were set as the control group and sandblasted, dual acid-etched H2O2/HCl-treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Several authors [27][28][29]52] have investigated the effect of HCl/H 2 O 2 treatment on the peri-implant bone formation. The osteoblastic response was improved for HCl/H 2 O 2 etched surface when compared to sandblasted one [52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors [27][28][29]52] have investigated the effect of HCl/H 2 O 2 treatment on the peri-implant bone formation. The osteoblastic response was improved for HCl/H 2 O 2 etched surface when compared to sandblasted one [52].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors [27][28][29]52] have investigated the effect of HCl/H 2 O 2 treatment on the peri-implant bone formation. The osteoblastic response was improved for HCl/H 2 O 2 etched surface when compared to sandblasted one [52]. Contradicting our results, Faverani et al [53] observed that double acid-etched reduced the corrosion stability of Ti\ \6Al\ \4V alloy in SBF containing different concentrations of dextrose and lipopolysaccharide versus machined surface.…”
Section: Discussionmentioning
confidence: 99%
“…The modification of the chemistry and phase compositions of the surface has been tested with success to improve both the biocompatibility and bioactivity of the titanium [4,5]. In order to achieve this purpose, coatings of calcium phosphates, oxides, hydroxides, and titanates have been used [6][7][8][9]. Also, the modification of the surface roughness and (or) topography has been successfully employed to enhance bioactivity on titanium and its alloys [7,10].…”
Section: Introductionmentioning
confidence: 99%
“…These properties determine which proteins will be adsorbed, the amount and the orientation they will have on the surface, thereby influencing mechanisms such as recruitment, adhesion, proliferation and cellular differentiation 6,18 . Thus, it is understood that the surface treatment of titanium also acts indirectly in osteoblast adhesion from the interaction with proteins that will mediate cellular adhesion and differentiation with contribution of proteins from the extracellular matrix, membrane and cytoskeleton 19,20 .…”
mentioning
confidence: 99%